Pengaruh Model Pembelajaran Treffinger Terhadap Hasil Belajar Matematika Siswa SD Negeri 37 Model Parepare - Zaid Zainal; Abdul Halik (Universitas Negeri Makassar, 2019)
This study examines the trial of treffinger learning models on mathematics subjects in elementary school students of SD 37 Model Parepare. The aim of this study was to find out whether there is an influence of Treffinger learning model on mathematics learning outcomes of students of SD Negeri 37 Model Parepare. This study uses a quantitative approach to the type of experimental research and uses the Quasy Experimental design in the form of The Nonequivalent Pre-test Post-test Control Group Design. The sampling technique used in this study was purposive sampling with a sample of 67 students. Data collection techniques used in this study were observation, tests in the form of multiple choices, and documentation. Data analysis uses descriptive statistical techniques and inferential statistics. The results of hypothesis testing using the Paired Sample T-Test test obtained significance of 0.00 (0.00 <0.05) and the results of the analysis of the t test obtained values - tcount <- t table (-17.999 <-2.037) indicate that H0 is rejected which means there are differences in the average mathematics learning outcomes of elementary school students 37 Model Parepare between before and after the use of the Treffinger learning model. Based on these results, it can be concluded that the Treffinger learning model influences the mathematics learning outcomes of students of SD Negeri 37 Model Parepare.